DIRECTIONS FOR IMPROVING THE ECONOMIC EFFICIENCY OF INDUSTRIAL ENTERPRISES OF HOUSING CONSTRUCTION IN UZBEKISTAN (World Economics and Finance Bulletin, 2023)
This article explores strategies to enhance the economic efficiency of industrial enterprises engaged in housing construction within Uzbekistan. The housing sector plays a crucial role in the country's economic development, and optimizing the operations of industrial enterprises can lead to significant improvements in cost-effectiveness, resource utilization, and overall productivity. This article proposes a multi-faceted approach encompassing various methods, case studies, and recommendations to achieve these goals.